Cybersecurity of Healthcare : Socio-technical Analysis and Solutions - Ewoh, Pius (Vaasan yliopisto, 2025)
The rapid digital transformation of health care systems and the widespread adoption of Electronic Health Records (EHRs) have significantly improved service delivery and information management. At the same time, these advancements have increased the vulnerability of health care systems to cyberattacks, data breaches and other security threats. This dissertation examines the key factors that contribute to cybersecurity vulnerabilities in health care from a sociotechnical perspective, emphasising the interaction between technology, humans and processes. Drawing on a synthesis of systematic and scoping reviews as well as conceptual and empirical analyses, the thesis identifies critical risk factors, including human error, outdated infrastructure, complex digital networks, insufficient training, non-compliance with regulatory requirements and delays in threat detection. The dissertation introduces and applies a sociotechnical cybersecurity framework and a privacy–security checklist model specifically designed for EHR environments. These models offer strategic guidance for strengthening cybersecurity in health care through proactive incident management, regulatory compliance, informed consent practices, staff training and the integration of automated threat detection systems. The dissertation highlights the importance of sociotechnical interaction and advocates a shift from reactive security measures to a proactive, integrated and human-centred cybersecurity approach in health care.

Sosiaali- ja terveydenhuollon järjestelmien nopea digitaalinen murros sekä sähköisten potilastietojärjestelmien (EHR) laajamittainen käyttöönotto ovat merkittävästi parantaneet palvelujen tuottamista ja tiedonhallintaa. Samalla nämä edistysaskeleet ovat kuitenkin lisänneet terveydenhuoltojärjestelmien haavoittuvuutta kyberhyökkäyksille, tietomurroille ja muille turvallisuusuhille. Tämä väitöskirja tarkastelee terveydenhuollon kyberturvallisuuden haavoittuvuuksiin johtavia keskeisiä tekijöitä sosioteknisestä näkökulmasta, korostaen teknologian, ihmisten ja organisatoristen prosessien välistä vuorovaikutusta. Tutkimus perustuu systemaattisten ja kartoittavien kirjallisuuskatsausten sekä käsitteellisten ja empiiristen analyysien synteesiin. Se tunnistaa keskeiset riskitekijät, kuten inhimilliset virheet, vanhentuneen infrastruktuurin, monimutkaiset digitaaliset verkostot, riittämättömän koulutuksen, sääntelyn noudattamatta jättämisen ja uhkien havaitsemisen viiveet. Väitöskirjassa esitellään ja sovelletaan sosioteknistä kyberturvallisuuden viitekehystä sekä yksityisyyden ja turvallisuuden tarkistuslistamallia, jotka on suunniteltu erityisesti EHR-ympäristöihin. Nämä mallit tarjoavat strategista ohjausta terveydenhuollon kyberturvallisuuden vahvistamiseen ennakoivan uhkien hallinnan, sääntelyn noudattamisen, informoidun suostumuksen käytäntöjen, henkilöstön koulutuksen ja automatisoitujen uhkien havaitsemisjärjestelmien integroinnin kautta. Väitöskirja korostaa sosioteknisen vuorovaikutuksen merkitystä ja puoltaa siirtymistä reaktiivisista turvallisuusstrategioista kohti ennakoivaa, integroitua ja ihmis-keskeistä lähestymistapaa terveydenhuollon kyberturvallisuudessa.
Keywords: data security; health service; data systems; cyber security; innovations; patient documents; risk management; data protection; fi=Tietojärjestelmätiede|en=Information Systems|